FROM COMPLIANCE TO CREDIBILITY: A BIBLIOMETRIC REVIEW OF REGULATORY FRAMEWORKS AND EXTERNAL ASSURANCE IN SUSTAINABILITY REPORTING - Edi Purwanto; Agustine Dwianika (Pasca Sarjana Universitas Satya Negara Indonesia, 2025)
This study conducts a comprehensive bibliometric analysis to map global research trends on regulatory frameworks, external assurance statements, and corporate sustainability reporting. Drawing on 2,468 documents from the Scopus database, it employs VOSviewer to visualize publication trends, co-authorship networks, citation patterns, and keyword co-occurrence. Results indicate a growing scholarly focus, especially from 2015 onwards, coinciding with regulatory developments and heightened sustainability expectations. The United States, United Kingdom, and European countries dominate contributions, while the Global South remains underrepresented. Influential authors such as Milne and Gray and Tsalis are identified as foundational voices. Thematic evolution reveals a shift from normative discussions toward technical and policy-driven inquiries. The study highlights emerging topics such as digital assurance and ESG integration while calling for greater inclusivity and interdisciplinary engagement. It provides critical insights for scholars, regulators, and practitioners committed to advancing credible, impactful sustainability reporting.